TECHNIQUES OF APPROACHING THE POLITICAL ISSUES IN TELEVISION INVESTIGATIVE PROGRAMS: AN ANALYTICAL STUDY - BushraDawoodSaba Al-Sanjari, seenhat Mohammed uldawody (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of this paper is to determine the methods of approaching the political issues in television investigative programs. It is based on the survey method and an analysis the content of a sample of the TV investigative show (The hidden is more immense) aired on Al Jazeera catellite channel. The study yields a number of results, the most important of which are: The experts category has ranked first among the sources on which these programs depend and at a percentage of (41.9%). The highest proportion of the meanings and ideas included in the program's episodes was for those related to violence, which reached a rate of (47.4%) while those pertaining to international terrorism reached (25%). The results showed a clear bias towards one side at the expense of the other in presenting the political issues. In light of the findings of this study, I put forward a series of recommendations. The most important of these can be summarised as follows: First, maximising the effectiveness of the TV investigative programs, by increasing the time space allocated to them. Secondly, supporting the crews of these programs financially and morally, as well as allowing them to participate in training courses organized by Arab and international TV networks specialized in the field of investigative journalism. The content of these programs must be kept out of alignment and imbalance in the presentation of information.